Optimizing sintering process to produce highest density of porous Ti-6Al-4V / Nor Hafiez Mohamad Nor ... [et al.] - Mohamad Nor, Nor Hafiez; Nor Hafiez, Hazran; Yahaya, Mohd Azman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Metal Injection Moulding (MIM) is a promising approach to produce to a near net-shape product of intricate geometry with cost-effective production. Nowadays, several researches have been done on implementing MIM to manufacture products by applying Titanium and its alloy as a main subject. Titanium and its alloys are renowned materials with good mechanical properties and high corrosion resistance. This study presents an optimization of sintering parameters for the highest density of porous Ti-6Al-4V powder mixed with 60wt% of palm stearin and 40wt% of polyethylene by metal injection moulding (MIM) technique. The density of the sintered part was resulted from tremendous densification of the sample. Sintering parameters have been optimized using Taguchi method of L9 (34) orthogonal array. The result from Taguchi method, combination of A2, B2, C1 and D1 as the best set of factors. This means that the sintering temperature at 1300oC; sintering duration, 120 min; heating rate 4oC/min and cooling rate 9oC/min were the optimum level that could statistically result in produce highest density of porous. The analysis of variance (ANOVA) was employed to determine the significant level (α) and its contribution to the variables of the final density. The study demonstrated that sintering temperature was the most influential variable contributed to the best final density, followed by sintering duration, cooling rate and heating rate.